The Influence Of Budget Planning, Regional Financial Information Systems, And Government Accounting Standards On The Quality Of Local Government Financial Reports (A Study On The Lebong Regency Government) - Purnamasari, Reni; Fitriano, Yun; Astuty, Kamelia (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2025)
Regional government accountability is demonstrated through the publication of regional government financial reports. Regional government financial reports serve as a means for local governments to account for their financial performance to the public. The purpose of this study was to determine the influence of budget planning, regional financial information systems, and government accounting standards on the quality of local government financial reports in Lebong Regency. The sample size for this study was 76 employees from 38 regional government agencies (OPD), with two employees per OPD. The data collection method was a questionnaire. The data analysis methods used were simple regression analysis, determination tests, and t-tests. The results of multiple linear regression testing obtained the regression equation Y = 6.635 + 0.399X1 + 0.230X2 + 0.231X3 with a positive regression direction, meaning that the increasing Budget Planning, Regional Financial Information Systems, Government Accounting Standards, the quality of regional government financial reports in Lebong Regency will increase. The test results for variable X1 (budget planning) have a significance value of 0.000 <0.05. This means that X1 (budget planning) has a positive and significant influence on the Quality of Government Financial Reports (Y) in Lebong Regency. Variable X2 (financial report accessibility) shows a significance value of 0.007 <0.05. This means that X2 (financial report accessibility) has a positive and significant influence on the Quality of Government Financial Reports (Y) in Lebong Regency. Variable X3 (regional financial accounting system) shows a significance value of 0.018 <0.05. This means that X3 (regional financial accounting system) has a positive and significant influence on the Quality of Government Financial Reports (Y) in Lebong Regency. The F-value is 0.000 < 0.05, indicating that X1, X2, and X3 collectively have a significant effect on the quality of Lebong Regency government financial reports (Y).